Servizio sociale e bioetica: cure palliative e amministrazione di sostegno nell’integrazione sociosanitaria (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
Social Work is present in welfare services and in health services where it contributes to social and health integration. The Social Work has been involved for some years in the bioethics committees for aspects of health and well-being of the person. Social Work can be inserted in the environmental context of a person's life by supporting his abilities of adaptation and coping, resilience, social support, even where suffering can be significantly high due to the consistent pathology such as that deriving from chronic-degenerative disease- oncology and possesses tools and expertise to protect people who live in such a condition of fragility.
Keywords: Social work; social and health integration; bioethics; palliative care; protection